A practical guide to the use of anti-epileptic drugs by neurosurgeons - Afshari, FT; Michael, S; Ughratdar, I; Samarasekera, S (Taylor and Francis, 2017)
Initiation of anti-epileptic drugs is increasingly relevant to daily neurosurgical practice. Intracranial pathologies ranging from brain tumours to subarachnoid haemorrhage and traumatic brain injury are commonly associated with the subsequent development of seizures. The scope and range of anti-epileptic drugs available has increased dramatically in recent years and understanding the evidence base behind this class of drugs in addition to their interaction/side effect profiles is essential. In this review we aim to generate a practical guide for neurosurgeons regarding the use of different anti-epileptic medications in common neurosurgical conditions, including considerations for their use in pregnancy.